2013
DOI: 10.3389/fphar.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules, Inhibitors of DNA-PK, Targeting DNA Repair, and Beyond

Abstract: Many current chemotherapies function by damaging genomic DNA in rapidly dividing cells ultimately leading to cell death. This therapeutic approach differentially targets cancer cells that generally display rapid cell division compared to normal tissue cells. However, although these treatments are initially effective in arresting tumor growth and reducing tumor burden, resistance and disease progression eventually occur. A major mechanism underlying this resistance is increased levels of cellular DNA repair. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 72 publications
1
130
0
2
Order By: Relevance
“…Recently, Ji et al, demonstrated that Ultra Violet (UV) radiation induced DNA-PKcs cytosol translocation and Sin1 association, which appeared required for mTORC2 activation and Akt phosphorylation (at Ser-473) [10]. Another explanation could be due to DNA-PKcs's ability to repair damaged DNA, which was observed in many cancer cells, serving as an important apoptosis resistance factor [11,31,32]. DNAPKcs inhibition, de-phosphorylation or depletion thus disrupts DNA repair process, and favors a pro-apoptosis outcome.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Ji et al, demonstrated that Ultra Violet (UV) radiation induced DNA-PKcs cytosol translocation and Sin1 association, which appeared required for mTORC2 activation and Akt phosphorylation (at Ser-473) [10]. Another explanation could be due to DNA-PKcs's ability to repair damaged DNA, which was observed in many cancer cells, serving as an important apoptosis resistance factor [11,31,32]. DNAPKcs inhibition, de-phosphorylation or depletion thus disrupts DNA repair process, and favors a pro-apoptosis outcome.…”
Section: Discussionmentioning
confidence: 96%
“…DNAPKcs is 460-kDa serine/threonine protein kinase, which belongs to phosphatidylinositol 3-kinase (PI3K)-like protein kinases (PIKK) family member [11,12]. Its main function is to dictate nonhomologous end joining (NHEJ) process thus repairing DNA double-strand breaks [11,12]. Studies have demonstrated DNA-PKcs overexpression/overactivation in CRC [13] and multiple other cancers, which regulates Akt-mTOR activation, and participates in oncogenic behaviors including cell survival, proliferation and radiation/chemotherapy resistance [9e11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that these molecules may be sensitize the effects of alkylators (25) and radiotherapy (26) specifically in glioma. Small molecule inhibitors of canonical NHEJ proteins, such as DNA-PK, have been developed and are now being tested as radiosensitizers in clinical trials, although currently there are no studies specifically in GBM (27). One concern regarding the clinical utility of these agents is the lack of a therapeutic index, since normal tissue typically relies on canonical NHEJ repair to address DNA damage induced by radiotherapy (28).…”
Section: Targeting Nhej and Hr Repairmentioning
confidence: 99%
“…Recent studies report that activating NHEJ repair through the interaction of the DNA-PKcs with its partners induces chemoresistance in cancer cells (10) and that inhibiting it induces chemosensitization (11). Thus, targeting the NHEJ pathway is an innovative cancer therapy strategy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%